Retraction Note: Effectiveness of Weekly Online Quizzes on 8th Grade Students English Test Scores - Ika Permata Sari; Muhammad Amin; Ahmad Junaidi (Tinta Emas Publisher, 2025)
Weekly online-based quizzes have been introduced as a strategy to enhance students academic achievement; however, their impact on test performance among 8th-grade students remains underexplored. At State Junior High School (SMPN) 1 Mataram, online-based quizzes have not yet been fully utilized as a learning tool. According to the Testing Effect Theory, frequent testing enhances memory recall and improves learning outcomes. This study aims to examine the effectiveness of weekly online-based quizzes in improving the English test scores of 8th-grade students. A quantitative research design was employed using a pre-test and post-test approach with 30 student participants. The results revealed a significant improvement in test scores, highlighting the positive impact of online-based quizzes on students academic performance. These findings suggest that integrating regular online quizzes into the learning process can be an effective strategy for reinforcing students understanding and retention of English concepts. Given the positive impact of online-based quizzes, it is recommended that educators incorporate them consistently into the curriculum to enhance student engagement and knowledge retention.